2012
DOI: 10.1016/j.aju.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Improving the compliance of the recurrent stone-former

Abstract: ObjectiveTo provide an overview of aspects of compliance by the recurrent stone-former, and to give recommendations for its improvement. About half of all stone-formers have one recurrence during their lifetime. To avoid recurrent stone formation it is necessary to use metaphylaxis, based on individual risks. However, all general and specific efforts are meaningless if patients are not willing or are incapable of following the proposed therapy in the long-term.MethodsPubMed was searched for articles on urolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A variety of dietary factors can be targeted for modification to reduce stone formation, including increasing fluids, maintaining normal calcium intake, limiting foods rich in oxalate, consuming sodium and animal protein in moderation and enriching the diet in fruits and vegetables ( Table 1 ). Specific dietary measures based metabolic testing and follow-up have been shown to be more successful than general dietary recommendations and no specific testing in preventing recurrent stones [24] . One study recommended that practitioners prioritize dietary recommendations, as three or few recommendations are associated with higher patient recall [25] .…”
Section: Dietary Managementmentioning
confidence: 99%
“…A variety of dietary factors can be targeted for modification to reduce stone formation, including increasing fluids, maintaining normal calcium intake, limiting foods rich in oxalate, consuming sodium and animal protein in moderation and enriching the diet in fruits and vegetables ( Table 1 ). Specific dietary measures based metabolic testing and follow-up have been shown to be more successful than general dietary recommendations and no specific testing in preventing recurrent stones [24] . One study recommended that practitioners prioritize dietary recommendations, as three or few recommendations are associated with higher patient recall [25] .…”
Section: Dietary Managementmentioning
confidence: 99%
“…Moreover, we wanted to find an appropriate mathematical expression that re-flects the relative risk of forming urine critically supersaturated with calcium oxalate (CaOx) and/or calcium phosphate (CaP) and the associated potential to initiate stone formation. If specific periods with individual high risk of crystallization can be defined, it would be possible, at least theoretically, to fine-tune recurrence prevention in a way that increases compliance [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution of crystals are among the most common interventions for the treatment of nephrolithiasis . Several studies have investigated the efficacy of dissolution therapies for different types of stones, including cysteine, struvite, and uric acid stones, all of which are found in kidney stones. ,, These therapies include dietary modifications which include encouraging individuals to drink more water than they normally do or through medications. ,, Recently, citrates have been used as dissolution agents for calcium crystals with the added aim of reducing calcium stone recurrence . Similarly, several studies have shown citrates to be more effective in dissolution of calcium crystals, compared to other dissolution agents, such as water alone and phosphates. , Nonetheless, it is most interesting to note that the recurrence rate among individuals who have received some form of intervention or treatment remains as high as 40%. ,, These recurrence rates suggest that current conventional therapies are not that effective.…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies have investigated the efficacy of dissolution therapies for different types of stones, including cysteine, struvite, and uric acid stones, all of which are found in kidney stones. 12,14,15 These therapies include dietary modifications which include encouraging individuals to drink more water than they normally do or through medications. 12,16,17 Recently, citrates have been used as dissolution agents for calcium crystals with the added aim of reducing calcium stone recurrence.…”
Section: ■ Introductionmentioning
confidence: 99%